Xenotransplantation of neonatal porcine bone marrow‐derived mesenchymal stem cells improves murine hind limb ischemia through lymphangiogenesis and angiogenesis. (6th May 2021) - Yamada, Hideaki; Sakata, Naoaki; Nishimura, Masuhiro; Tanaka, Tomoko; Shimizu, Masayuki; Yoshimatsu, Gumpei; Kawakami, Ryo; Wada, Hideichi; Sawamoto, Osamu; Matsumoto, Shinichi; Kodama, Shohta
Abstract: Background: The clinical utility of stem cell therapy for peripheral artery disease has not been fully discussed, and one obstacle is limited donor supplies. In this study, we attempted to rescue mouse ischemic hind limb by xenotransplantation of neonatal porcine bone marrow‐derived mesenchymal stem cells (npBM‐MSCs). Methods: Neonatal porcine bone marrow‐derived mesenchymal stem cells were transplanted to ischemic hind limbs of male C57BL/6J mice (npBM‐MSCs group). Mice with syngeneic transplantation of mouse BM‐MSCs (mBM‐MSCs group) were also prepared for comparison. The angiogenic effects were evaluated by recovery of blood flow on laser Doppler imaging, histologic findings, and genetic and protein levels of angiogenic factors. Results: Regarding laser Doppler assessments, blood flow in the hind limb was rapidly recovered in the npBM‐MSCs group, compared with that in the mBM‐MSCs group ( P  = .016). Compared with the mBM‐MSCs group, the npBM‐MSCs group had early and prominent lymphangiogenesis [ P  < .05 on both post‐operative days (PODs) 3 and 7] but had similar angiogenesis. Regarding genomic assessments, xenotransplantation of npBM‐MSCs enhanced the expressions of both porcine and murine Vegfc in the hind limbs by POD 3. Interestingly, the level of murine Vegfc expression was significantly higher in the npBM‐MSCs group than in the mBM‐MSCs group on PODs 3 and 7 ( P  < .001 for both). Furthermore, the secreted VEGFC protein level was higher from npBM‐MSCs than from mBM‐MSCs ( P  < .001). Conclusion: Xenotransplantation of npBM‐MSCs contributed to the improvement of hind limb ischemia by both angiogenesis and lymphangiogenesis, especially promotion of the latter. npBM‐MSCs may provide an alternative to autologous and allogeneic MSCs for stem cell therapy of critical limb ischemia.